Root Cause Analysis of Encumbrances Faced by Indigenous Building Contractors during Bidding in Nigeria - Ebekoziena, Andrew; Chibuike Nwaole, Angeline Ngozika; Lawrence Ibeabuchi, Aginah (School of Social Sciences, USM, 2017)
This paper intends to address one problem that is yet to be systematically examined. The focus is on the causal factors underlying the encumbrances faced by indigenous building contractors during bidding in Nigeria with a view to mitigating the hindrances and resultant effect of enhancing their business. To achieve this, data were collected via in-depth interviews and validated via secondary sources. Epistemology type of philosophical paradigm and random purposive sampling technique was adopted.Thematic analysis was adopted for the qualitative research and 2 themes were generated. Lagos State and Federal Capital Territory (FCT) were the locations covered. The participants were key practitioners (management and senior staff in procurement/estimating/tendering/bidding/contract administration department) in the contracting firms interviewed. A total of 16 firms were interviewed, eight from small and medium firms respectively. From the findings, all the participants agree that inability to bid for many projects, size of the project, location of the project, type of project, limited available personnel, the competition environment, lack of construction fund availability, and uncertainty of getting the job were identified as the major challenges facing indigenous building contractors in bidding performance. The study identified the root cause of each of the challenges and recommended that contractors should formulate right strategic plans, develop professionalism and innovative business strategies. Also, there is the need for building contractors to invest in talented staff, advanced construction technology, among others.